Determination of the Thevenin equivalent in power grids using real records based on short circuit power - A. Fonseca; G. Salazar; F. Quilumba; F. Pérez‐Yauli (IET Generation, Transmission & Distribution, 2021)
Abstract In recent years, methods for loadability determination based on real‐time measurements have been proposed for long‐term voltage stability scenarios. One of these methods corresponds to the reduction of the complete system into a basic Thevenin equivalent at a load bus. This paper proposes a method to determine the Thevenin equivalent at a load bus in power systems based on short circuit power (SSC) and its application to real records. The proposed Thevenin equivalent evaluation is performed by processing two consecutive sets of voltage magnitude and power measurements, both recorded at the same bus of a power system. This method establishes a Thevenin equivalent based on the determination of system's equivalent voltage (VS) which is obtained from SSC. This condition properly accounts for variable power factor load conditions and constant power factor alike in contrast with existing methodologies which assume constant power factor loads. The performance of this method is evaluated with real records from the Ecuadorian electric power system and contrasted by simulation.